Influences of pictogram‐based instructions in paediatric drug labelling on dosing accuracy among caregivers: a pilot study from Malaysia. Issue 2 (14th February 2017) - Chan, Huan‐Keat; Aswad, Edi; Ho, Yiing‐Ee
Abstract: Objectives: To investigate the influences of pictographic dosing instructions used in pediatric drug labeling on dosing accuracy. Methods: Children's caregivers who presented to a government‐funded hospital and received a short‐course antibiotic in liquid formulation were enrolled. They were randomized into two groups, receiving either a text‐only label (control; n = 31) or a pictogram‐plus‐text label (intervention; n = 32). Each participant was asked to measure the prescribed dose by using the label as the guidance, and dosing accuracy was assessed through direct observation. Key findings: The intervention group made significantly fewer errors than did the control group (unadjusted OR: 0.192 (95% CI: 0.037, 0.990); P = 0.043). Conclusions: By incorporating pictographic dosing instructions into the paediatric drug labelling, out‐of‐hospital medication errors can potentially be reduced.